2018
DOI: 10.1246/cl.180192
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Chemical Elements in the Reaction Cell of ICP-MS Based on the Affinities with Sulfur, Oxygen, and Fluorine

Abstract: Classification of chemical elements in the reaction cell of an inductively coupled plasma mass spectrometer (ICP-MS) was first reported based on the affinities with multiple elements, i.e. sulfur, oxygen, and fluorine. The data were summarized in the periodic table based on the affinity with each of the three elements mentioned above. An example of the application of the present results was illustrated by analyzing Y and La in the matrix of Sr and Ba, offering apparently improved background equivalent concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…These findings indicated that the reaction between Sr and O 2 was predominately confined to the affinity of one oxygen atom to one Sr atom. 24…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicated that the reaction between Sr and O 2 was predominately confined to the affinity of one oxygen atom to one Sr atom. 24…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the reaction between Zr and O 2 was not only confined to the affinity of one oxygen atom to one Zr atom. 21,24,25 Further oxygen atom transfer also occurred, even forming ZrO 3 + . The ion ratio of ZrO 3 + increased sharply from 0.09% (10% flow rate) to 25.41% (100% flow rate).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2006, Sugiyama and Nakano 2014, Bolea‐Fernandez et al . 2015, Zhu 2018, Resano et al . 2020, Harouaka et al .…”
mentioning
confidence: 99%
“…2015, Yamada 2015, Bolea‐Fernandez et al . 2017, Zhu 2018). These separations occur inline during the measurement, which results in quicker and more effective analyses.…”
mentioning
confidence: 99%